PERENCANAAN JADWAL INDUK PRODUKSI PADA PRODUK TEMPE DI RUMAH TEMPE INDONESIA - Bellinda Ayustina; Arief Nurdini; Ardhy Lazuardy (Asosiasi Dosen Muda Indonesia, 2023)
Rumah Tempe Indonesia is a business sector that produces various processed soybeans, one of which is tempeh with two brands, namely Tempekita and Tempe Kim's. Rumah Tempe Indonesia has also started implementing a make to stock production system in its business processes. However, until now Rumah Tempe Indonesia has not implemented a specific method to support the production system it implements. This production system can cause problems including the amount of production that does not match consumer needs, causing a shortage or excess of products which are very inefficient for the company's business continuity. These problems can be solved through production planning using the selected aggregate planning strategy or the strategy that produces the lowest total production costs. This strategy is implemented in the preparation of a production master schedule to estimate the quantity of tempe products that must be met in the next period. In this study, two strategies were used, namely the level strategy with a production cost of 1,403,904,740.04, - and the chase strategy with a production cost of 1,404,149,544.96, -. Based on these considerations of production costs, the strategy chosen to be continued in making the master production schedule is the level strategy. The Master Production Schedule is made based on the calculation results of the disaggregation process on the production units of each brand for each period. The amount of Tempekita and Tempe Kim's production based on the Master Production Schedule (JIP) respectively for the 1st period was 2790 and 13099 pcs, the 2nd period was 1901 and 10624 pcs, the 3rd period was 2104 and 10421 pcs, the 3rd period 4th period 3224 and 8897 pcs, 5th period 4196 and 8329 pcs, 6th period 4117 and 8004 pcs, 7th period 3735 and 8790 pcs, 8th period 4799 and 7726 pcs, 7th period 9th of 3700 and 7613 pcs, 10th period of 5409 and 7116 pcs, 11th period of 5329 and 6792 pcs, 12th period of 5070 and 7455 pcs.